IMPLEMENTASI NILAI-NILAI KEPEMIMPINAN YANG MELAYANI DALAM PENGEMBANGAN KARAKTER SANTRI DI PESANTREN DARUL IHSAN SAMARINDA - Alfiandy, Iqbal; Eka Wardhana, Kautsar (Journal of Sustainable Transformation, 2024)
This research explores the implementation of servant leadership values in developing student character in the Islamic boarding school environment. Islamic boarding schools as Islamic educational institutions have a strategic role in shaping students' character through formal and non-formal learning which is influenced by the leadership style of Islamic boarding school caregivers. This research used a qualitative approach with participatory observation methods and in-depth interviews. The research informants were Islamic boarding school leaders, caregivers, and students at the Darul Ihsan Islamic boarding school in Samarinda. The research results show that servant leadership values, such as empathy, commitment to student development, and example, are applied consistently by Islamic boarding school leaders in developing students' character. These values are transformed through daily interactions, spiritual formation, and religious-based self-development programs.Implementing servant leadership in Islamic boarding schools is not only influences students' moral and spiritual improvement but also increases their sense of social responsibility and discipline. This research concludes that servant leadership plays an important role in the character formation of students in Islamic boarding schools, and recommends this approach as an effective strategy for character education in Islamic educational institutions.